Axial crushing of triangular tubes - Fan, Zhihua. (2013)
In the present paper, the mechanical behavior of large deformation of a regular equilateral triangular tube under quasi-static axial crushing is reported, which is a polygon with an acute angle and odd number of sides. Based on the results from nonlinear finite element analysis (FEA), a new type of inextensional basic plastic collapse folding element is proposed to describe the plastic progressive collapse. The progressive folding around the stationary horizontal hinges and inclined traveling hinges are involved to develop the new basic folding element. Two types of inextensible deformation modes are discovered, i.e., diamond mode and rotational symmetrical mode. The average crushing load for each mode is predicted from the super-folding element theory, which was proposed from the previous investigation on the axial crushing of square columns. A rigid-plastic material model and a kinematically admissible model are involved in this theory. The results are further validated against experiments. The approximate quasi-static theoretical predictions for the mean crushing loads of triangular tubes provide reasonable agreement with the corresponding experimental results.